Localized rest and stress human cardiac creatine kinase reaction kinetics at 3 T. (28th March 2019) - Clarke, William T.; Peterzan, Mark A.; Rayner, Jennifer J.; Sayeed, Rana A.; Petrou, Mario; Krasopoulos, George; Lake, Hannah A.; Raman, Betty; Watson, William D.; Cox, Pete; Hundertmark, Moritz J.; Apps, Andrew P.; et al.
Abstract : Changes in the kinetics of the creatine kinase (CK) shuttle are sensitive markers of cardiac energetics but are typically measured at rest and in the prone position. This study aims to measure CK kinetics during pharmacological stress at 3 T, with measurement in the supine position. A shorter "stressed saturation transfer" (StreST) extension to the triple repetition time saturation transfer (TRiST) method is proposed. We assess scanning in a supine position and validate the MR measurement against biopsy assay of CK activity. We report normal ranges of stress CK forward rate (kf CK ) for healthy volunteers and obese patients. TRiST measures kf CK in 40 min at 3 T. StreST extends the previously developed TRiST to also make a further kf CK measurement during <20 min of dobutamine stress. We test our TRiST implementation in skeletal muscle and myocardium in both prone and supine positions. We evaluate StreST in the myocardium of six healthy volunteers and 34 obese subjects. We validated MR‐measured kf CK against biopsy assays of CK activity. TRiST kf CK values matched literature values in skeletal muscle (kf CK  = 0.25 ± 0.03 s −1 vs 0.27 ± 0.03 s −1 ) and myocardium when measured in the prone position (0.32 ± 0.15 s −1 ), but a significant difference was found for TRiST kf CK measured supine (0.24 ± 0.12 s −1 ). This difference was because of different respiratory‐ and cardiac‐motion‐induced B0 changes in the two positions. Using supine TRiST, cardiac kf CK values for normal‐weight subjects were 0.15 ± 0.09 s −1 at rest and 0.17 ± 0.15 s −1 during stress. For obese subjects, kf CK was 0.16 ± 0.07 s −1 at rest and 0.17 ± 0.10 s −1 during stress. Rest myocardial kf CK and CK activity from LV biopsies of the same subjects correlated ( R  = 0.43, p  = 0.03). We present an independent implementation of TRiST on the Siemens platform using a commercially available coil. Our extended StreST protocol enables cardiac kf CK to be measured during dobutamine‐induced stress in the supine position. Abstract : Changes in the kinetics of the creatine kinase shuttle are sensitive markers of cardiac energetics but are typically measured at rest and in the prone position. This study aims to measure CK kinetics during pharmacological stress at 3 T. We validate the MR measurement against biopsy assay of CK activity and evaluate normal ranges of stress kf CK in normal volunteers and obese patients. Our StreST protocol enables cardiac kf CK to be measured during dobutamine‐induced stress.